Comment on "Sedimentation Controls on Methane‐Hydrate Dynamics Across Glacial/Interglacial Stages: An Example From International Ocean Discovery Program Site U1517, Hikurangi Margin" by E. J. Screaton et al. (13th June 2020) - Sultan, Nabil
Abstract: In the IODP 372A proposal, working hypotheses used with respect to actively deforming gas hydrate‐bearing landslides were based on an initial calculation considering gas hydrate to occur in fresh water. This initial inaccuracy leads to predict the base of methane hydrate stability zone (MHSZ) to be at around 162 m below the seafloor (mbsf) at site U1517 while it is expected to be between 85 and 128 mbsf. It is most interesting that important negative chloride anomalies were measured well below the theoretical MHSZ without direct evidence of the presence of gas hydrate. These anomalies are usually a strong indication of gas hydrate occurrence. This initial inaccurate hypothesis provides the opportunity to evaluate the effectiveness of the indirect salinity detection method to quantify gas hydrate. Key Points: The IODP U1517 site was selected based on an initial hypothesis neglecting the effect of salt on the methane hydrate stability law Reported chloride anomalies are deeper than the methane hydrate stability zone at site U1517 Predicted methane hydrate (up to 68%) is not confirmed by direct evidence of the presence of gas hydrate nor by indirect seismic velocity